2017
DOI: 10.1039/c7py00013h
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particles composed of sphere-forming polystyrene-block-poly(t-butyl acrylate) (PS-b-PtBA) and control of surface morphology by homopolymer blending

Abstract: Submicron-sized virus-like particles comprising asymmetric PS-b-PtBA diblock copolymer particles having dot patterns on their surface were successfully prepared by a simple solvent evaporation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…For example, Robb et al described the use of self‐assembled nanoparticles from post‐modified poly(allyl glycidyl ether)‐ b ‐polylactide as modular delivery vehicles . Very recently, Hirai et al reported the preparation of virus‐like particles using an asymmetric polystyrene‐ b ‐poly( t ‐butyl acrylate) BCP and Schmidt et al that of reactive ellipsoidal striped nanoparticles from polystyrene‐ b ‐poly(2‐vinylpyridine) BCP blended with analogue functional homopolymers …”
Section: Introductionmentioning
confidence: 99%
“…For example, Robb et al described the use of self‐assembled nanoparticles from post‐modified poly(allyl glycidyl ether)‐ b ‐polylactide as modular delivery vehicles . Very recently, Hirai et al reported the preparation of virus‐like particles using an asymmetric polystyrene‐ b ‐poly( t ‐butyl acrylate) BCP and Schmidt et al that of reactive ellipsoidal striped nanoparticles from polystyrene‐ b ‐poly(2‐vinylpyridine) BCP blended with analogue functional homopolymers …”
Section: Introductionmentioning
confidence: 99%
“…As an example, the morphologies formed inside microspheres will transition between spherical, cylindrical, and lamellar with increases in the proportion of one polymer block . Figure a shows a poly(styrene ‐block‐ tert‐butyl acrylate) (PS‐ b ‐PtBA) microsphere obtained by the SORP technique that exhibits a dot‐like morphology . At a copolymerization ratio of almost 0.5, the morphologies of the block copolymers changed from spherical to cylindrical and then to lamellar.…”
Section: Controlling the Structures Of Phase Separated Polymer Microsmentioning
confidence: 99%
“…Block copolymer microspheres composed of a) PS‐ b ‐PtBA spheres (Reproduced with permission . Copyright 2017, Royal Society of Chemistry), and b) PS‐ b ‐PI cylinders and c) lamellae (Reproduced with permission .…”
Section: Controlling the Structures Of Phase Separated Polymer Microsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Hydrophobic homopolymers (HPs) have been found to be efficient morphology modifiers for BCP aggregates. [19][20][21][22][23][24][25][26][27] In most of the reported BCP/HP self-assembly systems, the molecular weight of the hydrophobic core-forming HPs is lower than or…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strategies such as introducing a second component, controlling copolymer composition, and altering self‐assembly condition have been applied to tune the morphology of BCP aggregates . Hydrophobic homopolymers (HPs) have been found to be efficient morphology modifiers for BCP aggregates . In most of the reported BCP/HP self‐assembly systems, the molecular weight of the hydrophobic core‐forming HPs is lower than or close to that of the core‐forming blocks in BCPs.…”
Section: Introductionmentioning
confidence: 99%